2010
DOI: 10.1007/s10560-010-0222-9
|View full text |Cite
|
Sign up to set email alerts
|

Developing an Additive Risk Model for Predicting Academic Index: School Factors and Academic Achievement

Abstract: The impact of school factors on academic achievement has become an important focus for identifying, preventing, and intervening with youth at-risk for academic failure. This study was designed to develop and test a more comprehensive school factor risk index. Specifically, the relationship between cumulative grade point average (GPA) and an additive risk index (ARI) were tested and an analysis of the index is presented. School factors that been shown in previous research to impact academic achievement were tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 58 publications
(63 reference statements)
0
12
0
5
Order By: Relevance
“…the participant's personal characteristics, family, school, peer and neighborhood factors. Such a pathway of accumulation of multiple risks has been tested in several studies with community-sample or referred subjects, demonstrating a significant linear relation between the cumulative risk index, computed by summing the number of dichotomized risk factors such as high vs. low IQ, secure vs. insecure attachment, or good vs. poor parenting for example, and children's or adolescents' externalizing or internalizing behavior (Appleyard, Egeland, van Dulmen, & Sroufe, 2005;Atzaba-Poria, Pike, & Deater-Deckard, 2004;Gerard & Buehler, 2004;Greenberg et al, 2001;Lanza, Rhodes, Nix, & Greenberg, 2010;Lucio, Rapp-Paglicci, & Rowe, 2011;Roskam, Meunier, Stievenart, & Noël, 2013;Trentacosta et al, 2008). Some of these studies were cross-sectional like the present one, and therefore unable to address the core question of the directionality of the effects (e.g., Atzaba-Poria et al, 2004;Greenberg et al, 2001).…”
Section: The Cumulative Effect Hypothesismentioning
confidence: 99%
“…the participant's personal characteristics, family, school, peer and neighborhood factors. Such a pathway of accumulation of multiple risks has been tested in several studies with community-sample or referred subjects, demonstrating a significant linear relation between the cumulative risk index, computed by summing the number of dichotomized risk factors such as high vs. low IQ, secure vs. insecure attachment, or good vs. poor parenting for example, and children's or adolescents' externalizing or internalizing behavior (Appleyard, Egeland, van Dulmen, & Sroufe, 2005;Atzaba-Poria, Pike, & Deater-Deckard, 2004;Gerard & Buehler, 2004;Greenberg et al, 2001;Lanza, Rhodes, Nix, & Greenberg, 2010;Lucio, Rapp-Paglicci, & Rowe, 2011;Roskam, Meunier, Stievenart, & Noël, 2013;Trentacosta et al, 2008). Some of these studies were cross-sectional like the present one, and therefore unable to address the core question of the directionality of the effects (e.g., Atzaba-Poria et al, 2004;Greenberg et al, 2001).…”
Section: The Cumulative Effect Hypothesismentioning
confidence: 99%
“…24,25 A method for understanding multiple risk factors is using an additive approach, where each risk factor is given equal weight and then risk factors are added together to identify the potential effect of co-occurring risks rather than the effects of specific individual risks. 26,27 This additive approach, to our knowledge, has only been used in a single study to examine co-occurring risk factors for inadequate cancer screening that included income, education, and health insurance, in white, black, Hispanic, and Asian women. 28 The study found that having more risks factors was associated with a lower incidence of preventive screenings.…”
Section: Introductionmentioning
confidence: 99%
“…Los factores de riesgo relacionados con la depresión son variados e incluyen desde aspectos biológicos hasta psicológicos y sociales. Los factores de riesgo se definen como aquellos atributos o variables que incrementan la probabilidad de que personas con características similares desarrollen alguna problemática (Lucio, Rapp-Paglicci, & Rowe, 2011). En el caso de la depresión, variables como la edad, el sexo, el divorcio, los problemas familiares y las características socioeconómicas de la región son algunos ejemplos de factores de riesgo (Díaz et al, 2006).…”
unclassified